2020
DOI: 10.3390/ijerph17030785
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Quality of Manuscripts Reporting on the Usability of Mobile Applications for Pain Assessment and Management: A Systematic Review

Abstract: Background: There has been increasing use of mobile mHealth applications, including pain assessment and pain self-management apps. The usability of mHealth applications has vital importance as it affects the quality of apps. Thus, usability assessment with methodological rigor is essential to minimize errors and undesirable consequences, as well as to increase user acceptance. Objective: this study aimed to synthesize and evaluate existing studies on the assessment of the usability of pain-related apps using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…), the results of this review suggest that there is the need to pay careful attention to quality as a considerable number of studies fail to report on pre-identified quality criteria. Nevertheless, these findings are aligned with the findings of previous reviews using the same quality scale, the CAUSS [30,78].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…), the results of this review suggest that there is the need to pay careful attention to quality as a considerable number of studies fail to report on pre-identified quality criteria. Nevertheless, these findings are aligned with the findings of previous reviews using the same quality scale, the CAUSS [30,78].…”
Section: Discussionsupporting
confidence: 88%
“…Although there might be reasons to develop or adapt a scale/questionnaire, its validity and reliability must be evidenced [77], which was not the case of the questionnaires used in 37% of the studies included in this review (i.e., [35,36,38,39,41,49,52,53,55,60,63,73]). The finding that SUS was the most commonly usability scale reported in the included studies (i.e., [43,45,54,56,58,59,61,[64][65][66][67][68][69][70][71]74]) is in line with a previous review on user-centered usability evaluation [78] and it suggests that this is a widely accepted instrument, usually regarded as a golden standard in terms of usability evaluation.…”
Section: Discussionsupporting
confidence: 84%
“…Examining how MUMentum and other interventions might impact pregnancy-specific anxiety is a worthy next step, as pregnancy-specific anxiety has been linked to length of gestation, low-birthweight, and adverse physical and mental health outcomes for offspring ( 60 ). Psychological intervention trials that can better tailor their content to fit specific and prevalent pregnancy-related worries stand to have particular impact on ethnic and racial minority women who are disproportionately likely to report high pregnancy-specific anxiety ( 6 , 61 , 62 ) and encounter adverse birth outcomes ( 63 ).…”
Section: Future Considerations To Improve Equity In Prenatal Anxiety ...mentioning
confidence: 99%
“…Usability is an essential criterion in the evaluation of mHealth apps [ 17 , 18 ] and has been defined as the extent to which a product can be used by users to achieve specific goals with effectiveness, efficiency, and satisfaction and in a specific context of use [ 19 ]. Nevertheless, a systematic review that synthesized and evaluated existing studies on the assessment of the usability of pain-related apps found 31 manuscripts on the usability of 32 pain apps [ 20 ]. The results of this systematic review suggested that several important methodological aspects regarding the assessment of usability are not being considered when developing pain-related apps, such as not using reliable and valid instruments to assess usability [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a systematic review that synthesized and evaluated existing studies on the assessment of the usability of pain-related apps found 31 manuscripts on the usability of 32 pain apps [ 20 ]. The results of this systematic review suggested that several important methodological aspects regarding the assessment of usability are not being considered when developing pain-related apps, such as not using reliable and valid instruments to assess usability [ 20 ].…”
Section: Introductionmentioning
confidence: 99%